2022
DOI: 10.1155/2022/6732914
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Calf Blood-Deproteinized Extract Ophthalmic Gel Combined with Sodium Hyaluronate Eye Drops on Conjunctival Hyperemia Score and Tear Film Stability in Patients with Dry Eye

Abstract: Objective. The aim of this paper is to research the impact of calf blood-deproteinized extract ophthalmic gel combined with sodium hyaluronate eye drops on conjunctival hyperemia score and tear film stability in patients having dry eye. Methods. 144 patients having dry eye disease who were hospitalized from July 2018 to July 2021 were chosen as the research targets, which were composed of the control group and research group on the basis of the sequences of hospitalization, and each has 72 cases. The sodium hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%